Differentiation and magmatism on the HED parent body - Ashcroft, H (2016)
The Howardite-Eucrite-Diogenite (HED) meteorites are a suite of basalts, cumulates and breccias which originate from one di↵erentiated parent body, and are linked to the asteroid Vesta. The HEDs are petrologically diverse with a range of major, minor and trace element compositions. Early crystallisation ages are recorded and so the HEDs provide us with a unique snapshot into the early solar system. The aim of this thesis is to investigate the petrogenesis of the eucrites and diogenites by addressing two questions. What is the Bulk Silicate Vesta (BSV) composition? What differentiation and magmatic processes have occurred? Putative BSV compositions were derived from the geochemistry of the meteorites and geophysical observations of Vesta. Series of one-atmosphere experiments and thermodynamic models investigated the BSV phase relations. Olivine crystallised at ∼1625 °C, followed by orthopyroxene at ∼1350 °C and feldspar at ∼1125 °C. Low-Ca pyroxene-melt partition coefficients for the minor and trace elements were measured. The compatibility of the REEs and HFSEs in low- Ca pyroxene increased by a factor of three, as temperature decreased from 1300-1125 °C and calcium content increased from Wo0.5-Wo8. These partition coefficients were combined with the observed phase relations to perform geochemical trace element calculations of differentiation and magmatic processes. My results suggest that BSV had an Mg#(100*(Mg/(Mg+Fe2+)) between 75-80, >43 wt. % SiO2, 2.5× CI refractory lithophile elements, 0.5 wt. % MnO and 0.75 wt. % Cr2O3. A three stage model for Vesta's evolution is suggested. Firstly, extensive if not global partial melting of BSV. Then, equilibrium crystallisation of the mantle and fractional crystallisation of mantle-derived melts produced diogenitic cumulates and eucrite liquids, accounting for the range in major and trace element abundances. The re-equilibration of trapped melt in cumulates is also thought to have occurred. Finally, crustal anatexis produced the range in trace element fractionations seen.